Manajemen Fisioterapi OA Genu Dekstra pada Pasien Obesitas dengan Modalitas dan Terapi Latihan - Rasyidi, Arba’Atur; Fatmarizka, Tiara; Kingkinarti , Kingkinarti (International Journal Labs, 2025)
Osteoarthritis (OA) of the knee is one of the most common degenerative joint disorders, particularly affecting the elderly and individuals with obesity, which can accelerate the progression of joint damage due to excessive mechanical load. Right knee OA (OA genu dextra) in obese patients can lead to reduced mobility, chronic pain, and decreased quality of life. This study aims to evaluate the effectiveness of physiotherapy management using a combination of infrared modality, transcutaneous electrical nerve stimulation (TENS), stretching, and strengthening exercises in reducing pain and improving knee joint function in an obese patient with right knee OA. The method used is a case study involving a 52-year-old female patient with a body mass index (BMI) greater than 38.7 kg/m², who underwent six physiotherapy sessions over three weeks. Evaluations were conducted using a goniometer to measure joint range of motion, Manual Muscle Testing (MMT) to assess muscle strength, the Visual Analogue Scale (VAS) for pain, and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) for joint function. The results showed a significant reduction in pain in the patient with right knee OA. The VAS score for tenderness decreased from 5/10 to 1/10, and for movement-related pain from 7/10 to 2/10. Muscle strength of the flexors and extensors improved from 2+ and 3+ to 4+ and 5, respectively, based on MMT. Knee flexion range of motion also increased from 75° to 125°, as measured by the goniometer. Additionally, the WOMAC score improved from 57.2% (severe category) to 23.9% (mild category), indicating enhanced daily activity function in the patient.